Clinical Consensus Statement: Balloon Dilation of the Sinuses. (February 2018) - Piccirillo, Jay F.; Payne, Spencer C.; Rosenfeld, Richard M.; Baroody, Fuad M.; Batra, Pete S.; DelGaudio, John M.; Edelstein, David R.; Lane, Andrew P.; Luong, Amber U.; Manes, R. Peter; McCoul, Edward D.; Platt, Michael P.; et al.
Objective: To develop a clinical consensus statement on the use of sinus ostial dilation (SOD) of the paranasal sinuses. Methods: An expert panel of otolaryngologists was assembled to represent general otolaryngology and relevant subspecialty societies. The target population is adults 18 years or older with chronic or recurrent rhinosinusitis (with or without nasal polyps, with or without prior sinus surgery) for whom SOD is being recommended, defined as endoscopic use of a balloon device to enlarge or open the outflow tracts of the maxillary, frontal, or sphenoid sinuses, as a standalone procedure or with endoscopic surgery. A modified Delphi method was used to distill expert opinion into clinical statements that met a standardized definition of consensus. Results: After 3 iterative Delphi method surveys, 13 statements met the standardized definition of consensus while 45 statements did not. The clinical statements were grouped into 3 categories for presentation and discussion: (1) patient criteria, (2) perioperative considerations, and (3) outcomes. Strong consensus was obtained for not performing SOD in patients without sinonasal symptoms or positive findings on computed tomography (CT) in patients with symptoms only of headache or sleep apnea without criteria for sinusitis. In addition, strong consensus was met that CT scan of the sinuses was necessary before performing SOD and that surgeons need to understand and abide by regulations set forth by the US Food and Drug Administration if they choose to reuse/reprocess devices. Conclusion: Expert panel consensus may provide helpful information for the otolaryngologist considering the use of SOD for the management of patients with a diagnosis of rhinosinusitis. This panel reached consensus on a number of statements that defined the use of SOD as inappropriate in the management of a variety of symptoms or diseases in the absence of underlying sinusitis. When patients meet the definition of chronic sinusitis as confirmed by CT scan, SOD of the sinuses can be indicated and/or effective in certain scenarios. Additional consensus statements regarding proper setting and safeguards for performing the procedure are described.